Semantics-based Framework for Incentivized Research Data Sharing - Kacy Adams; Deborah McGuinness; Oshani Seneviratne (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
We present a framework for incentivized research data sharing using an ontology called the Data Sharing Ontology (DSO). The DSO captures the semantics of academic research data sharing and provides an operational specification for data sharing between researchers. The DSO includes a two-part incentive mechanism to confirm citations and reward reproducible research methods. The proposed solution is demonstrated using a dataset-sharing decentralized application use case. The paper's contributions provide a scalable technique for creating, curating, publishing, and consuming web-based, structured, and reusable datasets, including semantically annotated knowledge graphs.